Gaya Komunikasi Digital: Peran Ucita Pohan dalam Mendorong Pemberdayaan Perempuan dan Self-acceptance di Instagram - Henyn Evelin; Aura Satria Tirta Iman; Latifa Ramonita (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Stereotypes and negative perceptions of women have existed from the past until today. With the advancement of time, social media platforms like Instagram have become a space for influencers to build businesses and share information, including Ucita Pohan, a mid-tier influencer. The problem statement in this research is how to analyze Ucita Pohan's communication style through Instagram in efforts to  build Woman empowerment and Self-acceptance since 2023. The research method used is descriptive qualitative, with primary data collected through direct and online interviews, as well as secondary data from literature sources. The findings reveal that Ucita Pohan underwent three processes in Fritz Heider's attribution theory, which underlie her actions in disseminating messages and support her current communication style. Additionally, she uses eight out of ten communication styles according to Robert W. Norton. Ucita Pohan creates high-quality content through her unique, cheerful, humble, and sincere character that resonates with her audience. This research is expected to contribute to the field of communication studies by providing insights into the communication styles of influencers in shaping the opinions and character of their followers. Additionally, this study enriches the discourse on women's empowerment and self-acceptance by demonstrating how an inclusive communication style can serve as a tool to promote women's empowerment in digital spaces.